Association between childhood maltreatment and atopy in the UK: A population based retrospective cohort study. (November 2022) - Nash, Katrina; Minhas, Sonica; Metheny, Nicholas; Gokhale, Krishna M.; Taylor, Julie; Bradbury-Jones, Caroline; Bandyopadhyay, Siddhartha; Nirantharakumar, Krishnarajah; Chandan, Joht Singh; Adderley, Nicola J.
Summary: Background: Childhood maltreatment affects over one in three children worldwide and is associated with a substantial disease burden. This study explores the association between childhood maltreatment and the development of atopic disease. Methods: We did a population-based retrospective matched open cohort study using participating general practices between 1st January 1995 and 30th September 2019. Read codes were utilised to identify patients exposed to childhood maltreatment (either suspected or confirmed) who were matched to up to four unexposed patients by age, sex, general practice, and Townsend deprivation quintile. Cox regression analysis was used to calculate adjusted (age, sex, Townsend deprivation quintile) hazard ratios (aHR) for development of atopy (asthma, atopic dermatitis, or allergic rhino conjunctivitis) during follow up in those without atopy at study entry. Results: 183, 897 exposed patients were matched to 621, 699 unexposed patients. During the follow up period, 18, 555 patients (incidence rate (IR) 28.18 per 1000 person-years) in the exposed group developed atopic disease compared to the 68, 368 (IR 23.58 per 1000 person-years) in the unexposed group, translating to an adjusted HR of 1.14 (95% CI 1.12–1.15). Notably, the risk of developing asthma was aHR 1.42 (95% CI 1.37–1.46). Associations were more pronounced in analyses restricted to females and confirmed cases of childhood maltreatment only. Interpretation: Considering the substantial health burden associated with childhood maltreatment, it is important to implement public health policies aimed at enhancing: 1) detection and primary prevention of childhood maltreatment, 2) secondary and tertiary prevention interventions to reduce the burden of ill health associated with exposure to maltreatment and 3) clinical awareness of such associations and subsequent knowledge of management. Funding: None.